Linking soil water balance with flood spatial arrangement in an extremely flat landscape - Vercelli, Natalia (2020)
In areas with very mild relief, water drains in a disordered way due to the lack of a developed drainage network, as it occurs in extremely flat sedimentary regions like the Argentine Pampas. The study analysed the flood spatial arrangements in 2014 by calculating landscape metrics and relating them to soil water balance. The study area is located at Del Azul creek lower basin (Pampa Ecoregion, Argentina). Daily soil water balances were obtained, and seven landscape metrics were calculated in 15 windows in five LandSat images, all along 2014, to explore the relationship between hydrological scenarios and spatial pattern summarized with principal component analysis. Water excess concentrated in winter (June and August); deficits were in late spring and summer (January and November), whereas the beginning of autumn (March) was an intermediate situation. Principal component 1 (44.7%) reflected area and shape metrics and correlated positively with water table level; principal component 2 (32.3%) summarized aggregation ones and was negatively associated with accumulated water excesses or deficits in previous 30 days and useful reserve. Both exhibited possible threshold-driven behaviour. Internal heterogeneity between NW and SE zones within the study area coincided with the existence of ancient alluvial fans. The results highlight the peculiarities of the flood spatial patterns in regions with very mild relief, where landforms usually determine water flows.